Inequality and poverty papers from the Society for the Study of Economic Inequality's inaugural meeting - Bishop, John; Amiel, Yoram (Emerald, 2007)
This volume is a collection of papers presented at the first meeting of the Society for the Study of Economic Inequality (ECINEQ). The Societys aims are to provide an international forum for all researchers interested in the study of economic inequality and related fields, bringing together the diversity of perspectives. The conference was held in Palma de Mallorca, Spain in July 2005. Over eighty parallel sessions were offered, providing novel and interesting work from both mature scholars and as well as new PhDs. With so much quality work from which to choose, it was necessary to limit the scope of Research on Economic Inequality, Volume 14.The first five papers all employ Spanish data and cover topics such as child poverty, social preferences toward redistribution, social exclusion, and multidimensional poverty. The next three papers examine inequality in the EU using alternative methodologies. Chapter Nine explores poverty dynamics among the elderly in Italy. Chapter Ten presents and extends the state of the art in multidimensional inequality measurement. Chapters Eleven and Twelve contribute to the theoretical underpinnings of inequality measurement. Chapters Thirteen through Fifteen contain analytical papers focused on evaluating the effects of public policy on poverty and inequality. The final two chapters use the questionnaire-experimental approach to examine individuals distributional preferences.This book is part of the Research on Economic Inequality series. It presents papers form the inaugural meeting of the Society for the Study of Economic Inequality (ECINEQ). It provides an international forum for all researchers interested in the study of economic inequality and related fields. It brings together a diversity of perspectives.
Keywords: Inequality -- Congresses.; Poverty -- Congresses.; elektronické knihy; electronic books